Considerations for the Successful Detection and Quantification of Genetically Modified Events in Grain and Food Samples Using Multiplex Digital PCR - Tigst Demeke (Foods)
The number of genetically modified (GMO) events for canola, corn, and soybean is steadily increasing. Some countries, including those in the EU, have regulatory requirements for the approval and use of plant ingredients containing GMOs. Multiplex digital PCR (dPCR) has been used for the simultaneous detection and quantification of various GMO events. This review covers the various factors to consider for multiplex digital PCR detection and the quantification of GMO events. DNA quality, quantity, and the presence of inhibitors are important factors to consider. Some dPCR instruments allow the use of multiple fluorescent dyes, which facilitates the setup of multiplex dPCR assays. This review focuses on the optimization of multiplex dPCR and describes the multiplex dPCR assays that have been reported for GMO detection.